Status and prospects of low carbon development in offshore oil and gas industry - CHEN Hongju, LIU Qiang, SUN Lili, YU Hang (Youqicang pingjia yu kaifa)
Under the “Dual Carbon” goals, achieving a green and low-carbon transformation in offshore oil and gas has become a significant challenge for enterprises. Based on an analysis of the current status of low-carbon development in the domestic and international oil and gas industries, and considering the characteristics of offshore oil and gas development in China, this study first examines the main measures and technologies adopted for green and low-carbon transformation in recent years from three aspects: establishing standards and source intensity analysis to strengthen source control, implementing clean energy substitution and energy efficiency improvement for process management, and end-of-pipe management through CO₂ geological storage, CO₂-EOR（Enhanced Oil Recovery）, and CO₂ hydrate storage. The emissions reduction effectiveness of various low-carbon technologies is clarified. Secondly, by analyzing the development level and roadmap of each technology, the study forecasts emissions reduction contributions of source carbon control, process management, and end-of-pipe storage technologies, and explores a low-carbon transformation pathway for offshore oil and gas to achieve carbon neutrality by 2050. Finally, the study proposes future directions for low-carbon development in offshore oil and gas, including collaboration between marine oil and gas and new energy, construction of new offshore oil and gas power systems, digital and intelligent offshore oil and gas development, large-scale offshore CCUS（Carbon Capture, Utilization, and Storage）, and marine carbon sinks. The findings can serve as a reference for the low-carbon development pathway of offshore oil and gas and provide insights for the green and low-carbon transformation of energy enterprises.